A narrative, child-participatory study of domestic mobility within grandmother-headed households in the Eastern Cape, South Africa - Lotter, Jaclyn Oehley (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
The movement of adults and children between households in South Africa is a tradition entrenched by apartheid state policies and fuelled by poverty and HIV/AIDS. Children affected by domestic mobility include not only orphans, but those whose families are struggling financially or are deprived of income through illness or death. One example of domestic mobility is the redistribution of children through grandmother-headed households. While domestic mobility has been researched from a number of different academic perspectives, there is scanty psychological literature on the subject, and a gap around children's experiences of their own mobility. Children's roles and agency in their mobility, and how these are shaped by their environments, social relations and resilience, are not considered. This research aimed to explore the meanings that domestic mobility had in the lives, identity constructions and personal narratives of South African children currently residing in grandmother-headed households in the Eastern Cape. This was achieved through a narrative approach, interested in big life-stories, as well as small stories of everyday interaction. Over the course of two years, five child participants aged between eight and 12 years constructed narrative material through participatory action research methodologies, including the mapping of time-lines and their lived environments, and photovoice. Child participants and their families were selected from the client-base of a non-governmental organisation, Isibindi (Alice). Narratives were analysed as case studies to tell detailed stories of children's lives, and to comment on issues associated with domestic mobility, socio-economic status, gender, education, HIV/AIDS and social protection. The study found that blanket definitions of poverty and domestic mobility conceal important variations in levels of poverty and individual experiences of mobility. While children are excluded from processes of decision-making about their mobility, they perform their agency by contributing to household survival and ensuring the continuation of mutually beneficial attachment relationships. This research argues that interventions which act on various systemic levels (macro, meso and exo) add support and protection for vulnerable children. This research also argues for psychological "scaffolding" of potentially traumatic or precarious processes, such as domestic mobility and deaths in families, through caregivers preparing and consulting with children before events happen.
Keywords: Women heads of households -- South Africa -- Eastern Cape; Poor women -- South Africa -- Eastern Cape; Migration, Internal -- South Africa; Poverty -- South Africa; HIV infections Social aspects -- South Africa; HIV infections Economic aspects -- South Africa; AIDS (Disease) Social aspects -- South Africa; AIDS (Disease) Economic aspects -- South Africa